The Implementation of Christian Virtual Counseling in STT Iman Jakarta to Increase the Resilience of Theological Students - Elsa Elsa; Maria Evvy Yanti (Budapest International Research and Critics University, 2022)
Anxiety, panic attacks, stress, and psychological fears are examples of life issues or suffering. Several students of STT Iman Jakarta who stay in dormitories have noticed and experienced this kind of situation. Every person's habit and lifestyle have been affected by the COVID-19 pandemic. Because this virus is so hazardous and threatens human life so quickly. Hence new government laws have been implemented Quarantine, like with the new normal life which means to stop the spreading of the covid-19 virus. STT Iman Jakarta has the same problem. This government regulation was used too at STT Iman Jakarta. Students are not permitted to engage in activities outside of the study area based. As a result, based on some students’ testimony who expressed their fear and pessimism in facing this pandemic. So, this study was carried out for this purpose. A mixed-methods methodology was used in this research. Connor Davidson is the instrument used to determine the amount of resilience. A closed-ended questionnaire was employed to assess the level of resilience. A Researcher has employed virtual